Comparative transcriptomic analysis reveals gene expression changes during early stages of Plasmodiophora brassicae infection in cabbage (Brassica oleracea var. capitata L.). Issue 2 (3rd April 2019) - Wang, Shenyun; Yu, Fangwei; Zhang, Wei; Tang, Jun; Li, Jianbin; Yu, Li; Wang, Hong; Jiang, Jiezeng
Abstract: Clubroot caused by Plasmodiophora brassicae is an economically important disease of crucifer crops throughout the world and is a major threat to the quality and yield of cabbage ( Brassica oleracea var. capitata L.) in China. Host resistance is essential for clubroot management. Although two cabbage lines (clubroot-resistant line CR21 and clubroot-susceptible line CS54) have been identified through screening 80 cabbage accessions, the molecular mechanisms underlying differential responses to clubroot remain elusive. Herein, RNA-seq analysis was performed to characterize the transcriptomic changes in CR21 and CS54 at 3 days after P. brassicae inoculation (DAI). In total, 1057 and 4741 differentially expressed genes (DEGs) were found in CR21 and CS54, respectively. Moreover, 541 genes were up-regulated in CR21, but showed either no significant change or were down-regulated in CS54. Gene Ontology (GO) analysis showed that most DEGs were involved in metabolism, transport, signal transduction and defence. Compared with the identified putative defence response genes in Arabidopsis thaliana, 165 resistance-related DEGs were obtained, including PAMPs-triggered immunity (PTI)-related genes and Effector-triggered-immunity (ETI)-related genes. Interestingly, the co-supported defence response DEGs contained the defence-related genes, wound response genes, RBOHB, WRKY28, TIR-NBS-LRR class ( RPS4 etc.), pathogenesis-related (PR) gene ( Bo7g005050 ), lipid transfer protein class ( LTP1 etc.), plant hormone-related genes, ethylene signalling transduction ( HRE1 -like gene and EIN3 ), ABA signalling ( PP2C and PYL13 ), and cell wall modification related genes ( EXP17 and PME44, beta-1, 3-glucanase and cytochrome P450 genes). Taken together, this study provided a comprehensive insight into transcriptomic responses to P. brassicae infection in two different cabbage lines, and identified several candidate genes that might contribute to clubroot resistance in cabbage and other Brassica crops.